Penentuan Kawasan Pariwisata Berbasis Komoditas Unggulan dan Pengaruh Beberapa Variabel Terhadap Pendapatan Asli Daerah Kota Magelang - Mochamad Ilham Diva Ramadhan; Ririt Iriani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Original Regional Income is regional income sourced from regional tax results, regional levy results, the results of separated regional wealth management, and other legitimate regional original income, which aims to provide a pass to regions in exploring funding in the implementation of regional autonomy as an embodiment centralized principle. Regional governments are expected to minimize the level of dependence on the central government regarding the management of regional revenues and expenditures. The target of regional development is the development of real, dynamic, harmonious and responsible regional autonomy with an emphasis on districts, cities and municipalities, increasing regional independence and increasingly coordinated development between sectors and between regions as well as between sectoral development and regional development. One component of regional development is tourism development. Magelang City is one of the areas frequently visited by tourists in Central Java Province. is located in a basin with a number of contributors to Magelang City's PAD, one of which is the tourism sector. This research aims to see the influence of Population Number, Number of Domestic Tourists, Number of Foreign Tourists on Regional Original Income (PAD) as well as looking at the leading commodities of tourism areas in Magelang City in 2013-2022. This type of research is quantitative descriptive, testing hypotheses and statistical data for certain uses, as well as time series data. Apart from that, it uses the Location Quotient (LQ) data analysis method, classical assumptions, multiple linear regression analysis, and hypothesis testing using the t test, F test, and Determination Coefficient (R2).